Maintenance strategy for old lathe machine in technical vocational education training institution - Khalid, Razni (2021)
Technical vocational education training (TVET) institutions in Malaysia provide competent and skilful future workers in line with the industrial requirement. Therefore, the facility where the students regularly doing practical such as workshop equipment should be at satisfactory condition and performance. However, due to poor machine care and maintenance, the condition and performance of the training equipment are not satisfactory. Most TVET institutions practice preventive and corrective maintenance, and all maintenance activities are done by suppliers. The current practice on maintenance has many issues such as high cost, delay, and sub-standard equipment maintenance quality. This situation is exacerbated when most machines especially the lathe machines have been used more than a decade. This situation has caused interruptions in teaching and learning. Therefore, the current practice of maintenance strategies needed to be reviewed. This study aims to develop a reliable maintenance strategy framework for TVET institutions. A case study in one TVET institution to examine critical success factors in maintenance strategy was conducted. The institution has 30 lathe machines. A total of 20 maintenance experts from TVET institutions and industries participated in the interviews. The Delphi method was used to gather the data from the experts. The findings on critical success factors revealed support of top management, involvement of all employees, skill training and education, recognition, enforcement, and continuous improvement should be integrated into the strategic and business plans. Next, the existing maintenance strategy, corrective and preventive maintenance together with total productive maintenance were analysed. The analyses were done using a combination of analytical hierarchy process (AHP) and Delphi method. The findings indicated that Total Productive Maintenance (TPM) is the most appropriate strategy to be implemented in the TVET institution. Then, the TPM strategy framework was developed using Interpretive Structural Modelling software. All the identified critical success factors of maintenance strategies were used as variables in the conception of the TPM framework. In addition, the group of experts involved in determining the relationship of the variables in the framework development. Finally, the TPM was evaluated on the 30 lathe machines in that institution. The performance of the TPM was then evaluated based on overall equipment effectiveness (OEE) formula, cost comparison and number of machine breakdown. The condition before TPM was introduced showed that the OEE performance of the machine was 58.2%. After a year of the implementation of TPM, the performance of OEE increased to 62.3% in the first semester and subsequently 64.1%. The result has exceeded the average OEE performance rate of 60% even though the machines have been in used more than a decade, which such a result is of a standard in the manufacturing industry. Also, the developed TPM framework has shown a reduction in maintenance cost and an improvement in the readiness of machine operation. Therefore, the framework is practical and proposed to be used as equipment maintenance strategy in TVET institutions.